STRATEGI KOMUNIKASI DIGITAL DAKWAH ISLAM DALAM MENJANGKAU GENERASI Z DIAKUN INSTAGRAM @LDK UIKA BOGOR - Hermansyah; Asep Gunawan, Noor Isna Alfaien (Jurnal Komunikasi, 2025)
The Lembaga Dakwah Kampus (LDK) AL INTISYAR UIKA Bogor is a campus da’wah institution focusing on da’wah content, visual da’wah, and creative da’wah. The da’wah content shared on the Instagram account @alintisyar_ldk attracts Generation Z. This research aims to understand how to determine engagingand relevant content for Generation Z on the Instagram account LDK AL Intisyar UIKA Bogor, as well as to explore the optimal utilization of Instagram features to enhance engagement and reach of da’wah messages among Generation Z on the LDK AL Intisyar UIKA Bogor Instagram account. This study employs a qualitative descriptive method. The findings conclude that the account @alintisyar_ldk has demonstrated a good understanding of these characteristics by presenting visually appealing content, such as high-quality images and videos, and highly informative info. This helps capture Generation Z's attention and maintain their engagement. The Instagram account @alintisyar_ldk has implemented effective strategies by actively interacting with followers through Q&A sessions, polls, and responding to comments. These strategies not only enhance engagement but also build a close relationship between the account managers and the audience. To further develop and increase appeal, it is recommended that the account continue to innovate by creating more varied content, such as collaborating with influencers or young figures, and hosting live sessions involving direct discussions with the audience